The Settler Order Framework: Rethinking Canadian Working-Class History - Burrill, Fred (Labour / Le Travail, 2019)
Canadian labour and working-class history has, to a great extent, been bedevilled in its attempts to understand national trends by the cleavages of gender, region, industry, race, language, and culture. This article argues that one possible way out of this impasse lies in foregrounding the particular relationship between colonial exploitation and class exploitation in our settler colonial economy, both in terms of class formation and in the ongoing project of social reproduction. The adoption of a “settler order framework” seeks to build on important recent works attempting to understand Indigenous peoples’ participation in the ranks of those who toil, struggle, and dream of freedom from capitalism, by integrating the fundamental reality of settler workers’ ongoing theft of Indigenous land and resources into the story of the Canadian working class.